Climate Change-Land Degradation-Food Security Nexus: Addressing India’s Challenge - Abrol, Inder; Gupta, Raj (Journal of Agronomy Research, 2019)
Monsoon rains provide relief from the sweltering summer heat conditions, replenish depleted profile moisture to breathe new life in soils. With appropriate management of rain water, Indian summer monsoons boost the level of ‘reservoir of life’. Our inability to manage spatial and temporal rainfall variation features of deficit and excess rainfall episodes and their interactions with soil variability is a major cause of uncertainty in agricultural production. In the past, entire focus of national efforts was on rainwater harvesting, storage and distribution through canal networks and greater reliance on ground water pumping to meet immediate crop water demands. These approaches have resulted in wide spread problems of natural resource fatigue and unsustainable water supplies. This paper analyses the complexities of climate change-land degradation-food security nexus and suggests the need for adopting alternate approaches emphasising on in situ conservation of rain water and its efficient use such as to reverse the processes that contribute to land degradation in specific landscapes.
Keywords: Summer monsoons; food security; land degradation; climate change; Kharif / Rabi fallow lands; yield stagnation; resource management